2001
DOI: 10.1038/sj.onc.1204663
|View full text |Cite
|
Sign up to set email alerts
|

E2F2 converts reversibly differentiated PC12 cells to an irreversible, neurotrophin-dependent state

Abstract: E2Fs play a central role in cell proliferation and growth arrest through their ability to regulate genes involved in cell cycle progression, arrest and apoptosis. Recent studies further indicate that this family of transcriptional regulators participate in cell fate/di erentiation events. They are thus likely to have a prominent role in controlling the terminal di erentiation process and its irreversibility. Here we have speci®cally examined the role of E2F2 in neuronal di erentiation using a gain-offunction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…NGF is known to regulate some members of the E2F family in PC12 cells (Persengiev et al, 1999(Persengiev et al, , 2001) and recent evidence indicates that E2Fs can transcriptionally regulate N-myc levels (Strieder and Lutz, 2003). We found that at 48 h NGF induced a 5.5-fold decrease in N-myc levels, a twofold decrease in E2F1 and a 2.8-fold decrease in E2F2 levels in 15N-TrkA (Figure 4b).…”
Section: Activation Of Trka Pathways Decreases Cell Numbermentioning
confidence: 52%
“…NGF is known to regulate some members of the E2F family in PC12 cells (Persengiev et al, 1999(Persengiev et al, , 2001) and recent evidence indicates that E2Fs can transcriptionally regulate N-myc levels (Strieder and Lutz, 2003). We found that at 48 h NGF induced a 5.5-fold decrease in N-myc levels, a twofold decrease in E2F1 and a 2.8-fold decrease in E2F2 levels in 15N-TrkA (Figure 4b).…”
Section: Activation Of Trka Pathways Decreases Cell Numbermentioning
confidence: 52%
“…Furthermore, E2F2 has been shown to have a tissue-restricted role in erythropoiesis and in neuronal differentiation. 22,23 Although structurally very similar to E2F2, E2F1 and E2F3 do not appear to inhibit DNA synthesis, 18,19,24,25 suggesting that this is a specific function of E2F2, not shared by the other members of the E2F subfamily. We have now investigated the role of E2F2 in regulating cellular proliferation.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…Thus the roles of E2F2 in either suppressing or promoting cell growth may be tissue specific. Indeed, E2F2 has been shown to have a tissue-restricted role in erythropoiesis and neuronal differentiation (13,31), and several studies have suggested that E2F2 may also be involved in apoptosis (43) although this still needs to be confirmed.One of the most paradigmatic models of cell-cycle progression is liver regeneration. Following partial hepatectomy (PH), 90 -95% of the remaining parenchymal cells synchronously reenter the cell cycle to begin regeneration (39).…”
mentioning
confidence: 99%
“…Thus the roles of E2F2 in either suppressing or promoting cell growth may be tissue specific. Indeed, E2F2 has been shown to have a tissue-restricted role in erythropoiesis and neuronal differentiation (13,31), and several studies have suggested that E2F2 may also be involved in apoptosis (43) although this still needs to be confirmed.…”
mentioning
confidence: 99%